(untitled) (Annals of Medical Research, 2024)
Aim: The aim of our study was to determine the optimal total core length for multiparametric magnetic resonance imaging (MpMRI)-guided prostate fusion biopsy (PFB) that would standardize clinical practice and maximize the detection rate of clinically significant prostate cancer (csPC) while reducing procedural complications, overdiagnosis, and cost. Materials and Methods: A total of 212 patients with at least 1 lesion with Prostate Imaging Reporting and Data System score of ≥3 were evaluated retrospectively. Biopsy core lengths from the lesions were summed, and total core lengths (TCL) were calculated. Multiple logistic regression analyses were conducted for PIRADS 3, 4, and 5 lesions and the effects of TCL on the detection of csPC were analyzed separately. Results: A total of 365 lesions were detected by MPMRI in 212 men included in the study. The mean TCL was 43.66 ± 12.91 mm in PIRADS 3 lesions, 47.71 ± 11.78 mm in PIRADS 4 lesions, and 60.36 ± 14.64 mm in PIRADS 5 lesions. As TCL increased, the probability of detecting both csPC (1.26-fold per unit increase in TCL) and clinically insignificant prostate cancer (cIPC)(1.25-fold per unit increase in TCL) increased for PIRADS 3 lesions at a statistically significant level,while for PIRADS 4 lesions, only the probability of detecting csPC (1.13-fold for each unit increase in TCL) increased. Conclusion: This study has shown that the frequency of PCa detection rises with increasing TCL. For PI-RADS 3, both csPC and cIPC rise with increasing TCL, whereas for PI-RADS 4 only the frequency of csPC rises.